1998
DOI: 10.4278/0890-1171-12.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Absenteeism: An Epidemiologic Study of 10,825 Employed Adults

Abstract: Obese employees tend to be absent from work due to illness substantially more than their counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 21 publications
4
59
0
7
Order By: Relevance
“…These findings are relevant to managers of health care systems for at least three main reasons; healthy staff attend work more regularly 28 , they counsel more regularly on healthy lifestyle habits and they do it more effectively. 6,15,16 The findings can help managers to target the groups of physicians who themselves are most in need of PA and health-related promotion.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are relevant to managers of health care systems for at least three main reasons; healthy staff attend work more regularly 28 , they counsel more regularly on healthy lifestyle habits and they do it more effectively. 6,15,16 The findings can help managers to target the groups of physicians who themselves are most in need of PA and health-related promotion.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the relation between obesity and sick leave, our results are consistent with reports of previous studies showing a significant association between sick leave among male and female workers and obesity. 1,[17][18][19][20]46 Four of these studies were studying only global obesity 17,18,46 or only body fat distribution 19 in relation with sick leave. Moreover, they rely on either cross-sectional data, 19 self-reported or past sick leave, 17,18,20 and none of them make a distinction between short and long spells of sickness absence.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Obesity is also associated with poor psycho-social functioning: depression, anxiety, stress, poor coping as well as psychological problems [11][12][13][14][15] and poor quality of life, 3,16 resulting in functional impairment and loss of working capacity. 17 Some authors studied the relation between sick leave and obesity 1,4,[17][18][19][20] and found a significant positive association. However, most of these studies do not take into account the body fat distribution; most are based on a crosssectional design and/or are based on self-reported sick leave.…”
Section: Introductionmentioning
confidence: 99%
“…Obese children, like obese adult workers, have been reported to experience higher rates of absenteeism. 27 In a study involving nine Philadelphia public schools, obese children had rates of school absenteeism that were 20 percent greater than those of their non-obese classmates. 28 Indeed, elevated body mass index (BMI) was a stronger predictor of absenteeism than traditional risk factors of age, sex, race, and socioeconomic status.…”
Section: Lost Productivity From Childhood Obesitymentioning
confidence: 99%